2004
DOI: 10.1002/ijc.20360
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐metastatic effect of capecitabine on human colon cancer xenografts in nude mouse rectum

Abstract: Key words: capecitabine; lymph node metastasis; lung metastasis; thymidine phosphorylase; rectal xenograft modelGastrointestinal cancer is one of the most common internal malignancies and is one of the leading causes of cancer-related morbidity and mortality in the world. The primary definitive treatment modality is surgical excision. Adjuvant therapies subsequent to surgery have been studied extensively in recent years because of the high incidence of postoperative recurrences. More than 40 years after its de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…The HT29 and HCT116 cells are highly metastatic, whereas DLD-1 are not in mouse xenograft models. 6,17,21 We found that both CXCR3 and CXCR4 were highly expressed in HT29 and HCT116 cells, whereas both receptors were hardly expressed in DLD-1 (Fig. 2a).…”
Section: Cancer Cell Biologymentioning
confidence: 89%
See 1 more Smart Citation
“…The HT29 and HCT116 cells are highly metastatic, whereas DLD-1 are not in mouse xenograft models. 6,17,21 We found that both CXCR3 and CXCR4 were highly expressed in HT29 and HCT116 cells, whereas both receptors were hardly expressed in DLD-1 (Fig. 2a).…”
Section: Cancer Cell Biologymentioning
confidence: 89%
“…18 We mainly used this pair of cell lines in this study, because they had the same genetic background with different metastatic potential. 19 To evaluate their metastatic activities in vivo, we performed the orthotopic transplantation model of CRC metastasis in mice 6,17,20 with the use of GFP marker. After injecting the cells into the rectal smooth muscle layer of nude mice, we macroscopically examined metastatic foci using GFP fluorescence.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…At day 14 or 28, the para-aortic LNs were dissected and pooled for each mouse to quantify the metastasized cells by quantitative PCR (Ninomiya et al, 2004). All animal experiments were approved by the Animal Care and Use Committee of Kyoto University.…”
Section: Methodsmentioning
confidence: 99%
“…The rectal xenograft method offers a convenient animal model for colorectal cancer that can metastasize to the draining para-aortic LNs (Kashtan et al, 1992;Tsutsumi et al, 2001;Ninomiya et al, 2004). For example, it was reported that HT29 metastasized to LNs in all tumor-bearing mice (10/10) (Tsutsumi et al, 2001), whereas LS174T did not (0/5) (Kashtan et al, 1992).…”
Section: Expression Of Chemokine Receptors Cxcr3 Cxcr4 and Ccr7 In Cmentioning
confidence: 99%
See 1 more Smart Citation